Penerapan Raf’u al-H?araj; Studi Analisis Shalat Jamak fî al-H?ad?ar li al-H?âjah - Ahmad Faisol (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2017)
In Islam, Raf’u al-H?araj are basic principles in Islamic law that eliminates legal imposition on everything that complicate accordance with mashaqqah categories of human needs that level is divided into dar?riyyât, h?âjiyyât, tahsîniyyât with ease and tolerance are form of legal relief (takhfîf).One form of takhfîf in islam is plural prayer. Because the ability to do the plural pray agreed by scholars is when traveling, pain, rain, and because of the Hajj. While the plural prayer is because there is a flurry of travel because when not in al-h?âjah (fi al-had?ar li al-h?âjah) for people who are not accustomed still a debate among scholars. The debate is interesting to observed with regard to the context of the passage by doing in-depth study of the interpretation of its meaning, as well as wujûh al-dilâlah of the passage, what is ta’abbudî which leaves no room for ijtihad, or ta’aqqulî are still opportunities ijtihad in istinbât? her, as well as other relevant considerations in accordance with the provisions of maqâs?id al-sharî’ah. This study provides an interesting conclusion that plural prayer is allowed, the record should exist mashaqqah in accordance with the principles of Raf’u al-H?araj and plural prayer does not become a habit.